2020
DOI: 10.1038/s43247-020-00057-8
|View full text |Cite
|
Sign up to set email alerts
|

Chance played a role in determining whether Earth stayed habitable

Abstract: Earth’s climate has remained continuously habitable throughout 3 or 4 billion years. This presents a puzzle (the ‘habitability problem’) because loss of habitability appears to have been more likely. Solar luminosity has increased by 30% over this time, which would, if not counteracted, have caused sterility. Furthermore, Earth’s climate is precariously balanced, potentially able to deteriorate to deep-frozen conditions within as little as 1 million years. Here I present results from a novel simulation in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Timothy M. Lenton, (Lenton et al 2020) point out that "climatologists missed it because Life is hard to see in the Earth's energy balance" and the "scientists were repelled by teleological arguments". Toby Tyrrell, in spite of the discrepancies he expresses with the Gaia theory, accepts that it is a problem, and that this presents a puzzle (Tyrrell 2020). Science is not evolution, it is also evolution.…”
Section: From Ananthropological Point Of Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…Timothy M. Lenton, (Lenton et al 2020) point out that "climatologists missed it because Life is hard to see in the Earth's energy balance" and the "scientists were repelled by teleological arguments". Toby Tyrrell, in spite of the discrepancies he expresses with the Gaia theory, accepts that it is a problem, and that this presents a puzzle (Tyrrell 2020). Science is not evolution, it is also evolution.…”
Section: From Ananthropological Point Of Viewmentioning
confidence: 99%
“…Toby Tyrrell (2020) criticizes the concept of "change" in the Gaia Hypothesis: "the Gaia hypothesis lacks a clear mechanistic basis", i.e., it happens sometimes by chance. The concept of the "cosmic miracle" is controversial for science.…”
Section: From Ananthropological Point Of Viewmentioning
confidence: 99%
“…In terms of the carbon cycle, a related insight is that input fluxes of CO2 into the ocean-atmosphere system on geologic timescales must have remained largely equal to the output fluxes (Berner & Caldeira 1997). Nevertheless, the idea that these observations necessarily imply a stabilizing feedback has been challenged (Tyrrell 2020).…”
Section: Stabilizing Mechanisms In the Carbon Cyclementioning
confidence: 99%
“…The last set of parameters are intimately related with the issue of habitability and the long term conditions to support a stable climatic system. A recent simulation in which thousands of planets were assigned randomly generated climate feedbacks to verify whether habitable conditions remained over a period of 3 billion years showed that chance plays a role, meaning that Earth-like long lasting habitability is most likely a contingent rather than an inevitable outcome [28].…”
Section: Planetary Classification Schemementioning
confidence: 99%